Furin and COVID-19: Structure, Function and Chemoinformatic Analysis of Representative Active Site Inhibitors - Villoutreix, Bruno O.; Badiola, Iker; Khatib, Abdel-Majid (Frontiers in Drug Discovery, 2022)
Furin is involved in the endoproteolytic processing of various protein precursors implicated in many diseases such as diabetes, obesity, atherosclerosis, cancer, Alzheimer's disease and viral infection including COVID-19. Recently, cell entry of SARS-CoV-2 was found to require sequential cleavage of the viral spike glycoprotein (S protein) at the S1/S2 and the S2ʹ cleavage sites. The S1/S2 site (PRRAR) can be cleaved by the proprotein convertase furin that facilitates membrane fusion and viral spread. Here we summarized the recent findings on furin and S protein structures, the role of S protein cleavage by furin during SARS-CoV-2 infection. We analyzed 12 diverse representative inhibitors of furin using a chemoinformatic approach starting from a list of 628 compounds downloaded from the ChEMBL database. Among those, only 76 survived a soft rule of five filtering step. Structural alerts are present on most of these molecules while some compounds are also predicted to act on toxicity targets. No clinical trials are presently listed at the ClinicalTrials.gov website regarding small molecule inhibitors of furin.